2016
DOI: 10.18569/tempus.v10i1.1604
|View full text |Cite
|
Sign up to set email alerts
|

Perfil epidemiológico das vítimas dos acidentes de transporte, registrados nos serviços sentinelas da rede viva no município de Cuiabá-MT, 2011

Abstract: Objetivos: Descrever o perfil das vítimas de acidentes de transportes atendidos em três unidades de referência em urgência e emergência na capital de Mato Grosso. Métodos: Estudo descritivo, de corte transversal, com base nas informações sobre as vítimas de acidentes de transporte notificadas em 2011 pelo Projeto VIVA em Cuiabá-MT. Resultados: Em 2011, 241 vítimas de acidentes de transporte foram notificadas (32,1% dos atendimentos). A maioria das vítimas era do sexo masculino (71,4%), jovens (38,4%), de cor d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…10 In another study, the SAMU vehicles were the second most used pre-hospital transportation (11% of the participants), and vehicles from the Serviço Integrado de Atendimento ao Trauma e Emergência (SIATE) [Trauma and Emergency Care Integrated Service] were used by most of the patients (75%). 11 Silva, Galvão and Muraro (2016) showed that the transports most used by victims to reach urgency and emergency units were private (48.5%) and SAMU (34.4%) vehicles, respectively. 12 Riders are the most prevalent victims and motorcycles are present in most accidents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 In another study, the SAMU vehicles were the second most used pre-hospital transportation (11% of the participants), and vehicles from the Serviço Integrado de Atendimento ao Trauma e Emergência (SIATE) [Trauma and Emergency Care Integrated Service] were used by most of the patients (75%). 11 Silva, Galvão and Muraro (2016) showed that the transports most used by victims to reach urgency and emergency units were private (48.5%) and SAMU (34.4%) vehicles, respectively. 12 Riders are the most prevalent victims and motorcycles are present in most accidents.…”
Section: Discussionmentioning
confidence: 99%
“…11 Silva, Galvão and Muraro (2016) showed that the transports most used by victims to reach urgency and emergency units were private (48.5%) and SAMU (34.4%) vehicles, respectively. 12 Riders are the most prevalent victims and motorcycles are present in most accidents. Moderate TBI was prevalent in these variables.…”
Section: Discussionmentioning
confidence: 99%